Expenditure Composition and Economic Development in Benin - Pani, Marco (Departmental Papers; Departmental Paper ;, 2010)
This paper analyzes expenditure composition and economic development in Benin. It addresses some specific issues on the basis of a stylized model of the Beninese economy that highlights the tradeoff between expenditure on wages and investment. The model takes into account specific characteristics of the Beninese economy, including the large share of agriculture in employment and GDP, the large number of urban unemployed engaged in precarious informal sector activities, and the strong influence of labor unions in the formal labor market concentrated in the urban areas.